Legacies of the past : memory and trauma in Mexican visual and screen cultures - Thornton, Niamh; Haddu, Miriam, 1971- (Edinburgh : Edinburgh University Press, 2020)
Riven with unresolved traumas and appropriated by successive governments, the past haunts spaces in Mexican film and visual culture. These events, without consensus or a singular/unifying narrative, act like spectres haunting the present. To comprehend how they manifest, Legacies of the Past considers how filmmakers and visual artists have found ways of understanding these haunted spaces. With case studies of films like El atentado (2010), Flor en Otomi (2012) and the photography of Dulce Pinzon, this collection analyses the audio-visual representations of several heightened events in Mexican history. The contributors' explorations, imaginings and counter-imaginings bring the past to the foreground, creating new narratives and proposing new histories in order to show the significance of storytelling and narrative for a shared understanding of ourselves.
Introduction: Legacies of the past : memory and trauma in Mexican visual and screen culture / Niamh Thornton -- On the commemoration of Mexico '68 : Los agachados de Rius, número especial de los cocolazos de julio-agosto-septiembre y octubre quién sabe si tambor... / Chris Harris -- Felipe Cazals and Servando González Grapple with the aftermath and the archive : 1976 and 1968 / Niamh Thornton -- Spectres of Mexico's 'dirty wars : gendered haunting and the legacy of women's armed resistance in Mexican documentary film / Viviana MacManus -- Stages for an assassination : roles of cinematic landscape in Jorge Fons' El atentado (2010) and Carlos Bolado's Colosio: el asesinato (2012) / Maximiliano Maza-Pérez -- Aliens as superheroes : science fiction, immigration and the photography of Dulce Pinzón's 'The real stody of the superheroes' / Catherine Leen -- #YoSoy132 as a continuation of the 1968 Legacy / Jessica Wax-Edwards -- Loss and mourning in documentary : Tatiana Huezo's Ausencias (2015) / Miriam Haddu -- Teresa Margolles' work with space : ruins, resonances and the echo of the absent / Julia Banwell.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Motion pictures -- Mexico -- History; Psychic trauma in motion pictures; Mexico -- In motion pictures; Mexico -- History; Cinéma -- Mexique -- Histoire; Traumatisme psychique au cinéma.; Mexique -- Histoire; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Psychic trauma in motion pictures; Mexico; Electronic books; History